Experimental evaluation of a radiant heated floor coupled to an air-to-water heat pump for the cooling of greenhouses - Valiño, V.; Perdigones, A.; García, J.L.; Luna, L. (Spanish Journal of Agricultural Research, 2010)
This paper describes the experimental cooling of a greenhouse in Madrid (Spain) using a radiant heated floor (RHF) coupled to an air-water heat pump (HP). Two cooling scenarios were studied over the summers of 2005 and 2006: natural ventilation + a shading screen (control system), and natural ventilation + a shading screen + an RHF (concrete) coupled to an air-water heat pump (i.e., in cooling mode; nominal power, 34.1 W m–2). Using the difference between the outside and inside air temperatures, it was concluded that at 0.5 m above the floor the RHF system reduced the temperature by 1.1°C in 2005 and 0.8°C in 2006. Both cooling scenarios were compared with other cooling technologies: the use of the natural ventilation + shading + RHF gave a smaller air temperature difference than fogging at a height equal to or lower than 0.5 m. A model based on the heat pump performance curves was constructed to predict its power consumption and good predictions of the variation over the day were obtained. The power consumption of the heat pump was 104.8 Wh m–2 d–1 (from 13:00 to 18:00 h) under our test conditions in Madrid. The RHF-HP system may only be appropriate for cooling greenhouses under certain circumstances, e.g., when growing high value crops or when cost is not a limiting factor, as its initial investment cost is about € 38 m–2.